2019
DOI: 10.1111/acfi.12560
|View full text |Cite
|
Sign up to set email alerts
|

Is better banking performance associated with financial inclusion and mandated CSR expenditure in a developing country?

Abstract: Motivated by legislation mandating CSR expenditure to improve social equality and economic development in India, we examine the association of CSR expenditure and financial inclusion with the performance of banking firms in the period after introduction of the legislation. We study whether mandated CSR expenditure and/or financial inclusion measures are associated with better financial performance, using both accounting and stock market measures of performance, for Indian banks during 2015–2017. Our results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 70 publications
2
35
2
Order By: Relevance
“…For instance, Mendoza et al (2009), studying international financial integration during the 1980s, find a negative relationship between financial access and non-performing loans in countries with deep financial market borrowing. Similarly, Bhattacharyya et al (2020) confirm no association between financial inclusion and market-based banks' performance in India between 2015 and 2017.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…For instance, Mendoza et al (2009), studying international financial integration during the 1980s, find a negative relationship between financial access and non-performing loans in countries with deep financial market borrowing. Similarly, Bhattacharyya et al (2020) confirm no association between financial inclusion and market-based banks' performance in India between 2015 and 2017.…”
Section: Introductionmentioning
confidence: 70%
“…Similarly, Dabla-Norris et al (2015) and Sarma and Pais (2011) conclude that adverse effects can be found from financial inclusion on bank's non-performing loans and that nonperforming assets are inversely associated with financial inclusion, indicating that greater financial inclusion has not contributed to the performance of the banking system. No link between expenditure on corporate social responsibility, financial inclusion, and marketbased bank's performance was found in Bhattacharyya et al's (2020) study using a sample of Indian banks covering the period 2015-17.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Together with clients, employees have been added as another relevant stakeholder, and one for whom sustainable banking also has effects [76][77][78][79]. In the line of CSR performance, which is more central in this second period, one finds a large quantity of studies that border the relationship between surrender of corporate social responsibility and financial performance [6,[80][81][82][83][84][85][86][87][88][89][90][91][92]. One explanation of such significant growth in the works in this area is that it is due to the availability of new sources of data that consider measurements of CSR performance.…”
Section: Discussionmentioning
confidence: 99%
“…In much smaller measure, but also of interest, some studies border a middle area, which is the relationship between CSR performance and corporate reputation [10,13]. In the field of studies that are more about banks' behavior in CSR, noteworthy studies include some that have addressed financial inclusion [6,87,93], about CSR reporting and Global Reporting Initiative [94][95][96][97][98], not forgetting studies that continue the line of Socially Responsible Investment [99,100]. Finally, it is also interesting to note how in this last period, various studies that consider the theme in developing countries have emerged [58,[101][102][103][104][105][106].…”
Section: Discussionmentioning
confidence: 99%